Forest schooling as a supplement to school education - Strumińska-Doktór, Anna; Jagodzińska, Małgorzata (Studia Ecologiae et Bioethicae, 2018)
The article analyses the essence of forest education in the context of its impact on shaping children’s attitudes. Referring to examples of forest activities, less structured than activities in school classes and allowing for greater independence for children, it argues for using various forms of forest education, because direct contact with the forest gives better opportunities to know, discover and understand nature and shape a culture of communing with the forest. At the same time, the importance of the forms and content of forest education for shaping pro-social attitudes is emphasised. Children with greater freedom of action learn to solve problems, make decisions, create rules and observe them and treat the forest environment with respect, which translates into respect for the whole world around them.